Predictors of Neonatal Mortality in a Tertiary Institution of a Developing Country - Komomo Ibor Eyong (Iranian Journal of Neonatology, 2020)
Background: Nigeria continues to have one of the highest rates of neonatal deaths in Africa. Hospital-based studies had implicated prematurity, neonatal sepsis, poor antenatal care, and perinatal asphyxia as major causes of neonatal mortality. This study aimed to highlight the predictors of neonatal deaths and offer solutions to reduce them.Methods: This 5-year retrospective review investigated the neonatal mortality rate at the University of Calabar Teaching Hospital from 2013 to 2018. The demographic characteristics, clinical parameters, duration of hospital stay, and challenges encountered in managing the patients were documented in this study. The obtained data were analysed in SPSS software (version 26).Results: Neonatal mortality rate of 60 per 1000 live births was recorded in this study. The major causes of death were prematurity (n=86, 39.8%), perinatal asphyxia (n=45, 20.8%), neonatal sepsis (n=37, 17.1%), and congenital malformation (n=34, 15.7%). Low socioeconomic class and out-born were additional risk factors in this regard.Conclusion: The neonatal mortality rate is higher than the average national rate and the figure obtained in the same center more than a decade ago. Infrastructural decay during the study period may partly explain the high neonatal mortality rate. Enhancement of the infrastructure and use of kangaroo mother care are recommended to reduce neonatal death, especially among premature babies.